设P(A)= a,P(B)= b, P(A+B)= c, 则 为: ( )5ccb36b4af534c44718217f75fa8529b.gif
c-b
举一反三
- 设P(A)= a,P(B)= b, P(A+B)= c, 则 为: ( )5ccb36b4af534c44718217f75fa8529b.gif
- 设P(A)= a,P(B)= b, P(A+B)= c, 则 P(AB)为:
- 设事件A与B为随机事件,则下列正确的是( ) A: P(A+B)=P(A)+P(B) B: P(AB)=P(A)P(B) C: P(A+B)=P(A)+P(B)-P(AB) D: P(A)=P(A|B)
- 设A、B为两事件,P(A)=0.7,P(B)=0.6,,则P(A+B)=_______,P(AB)=,=_______,=_______,
- 设A、B为两事件,P(A)=0.7,P(B)=0.6,P(B∣A)=0.6,则P(A+B)=()。
内容
- 0
设事件A,B满足P(A+B)=P(A)+P(B),则().
- 1
设A、B为随机事件,且P(A)=0.5,P(B)=0.6,P(B|A)=0.8,则P(A+B)=?
- 2
设A ,B 为随机事件,且P(A)=0.5,P(B)=0.6,P(A+B)=0.7,则P(B∣A)=( )
- 3
设事件A与B为随机事件,则P(A+B)=( ) A: P(A)+P(B) B: P(A)+P(B)-P(A)P(B) C: P(A)+P(B)-P(AB) D: P(A)+P(B)[1-P(A)]
- 4
在域F中,设其特征为p,对于任意a,b∈F,则(a+b)P 等于ap+bp